2006
DOI: 10.1387/ijdb.052100cc
|View full text |Cite
|
Sign up to set email alerts
|

Germ-plasm specification and germline development in the parthenogenetic pea aphid Acyrthosiphon pisum: Vasa and Nanos as markers

Abstract: The germarium, oocytes and embryos of the parthenogenetic viviparous pea aphid Acyrthosiphon pisum are contained within a single ovariole. This species provides an excellent model for studying how maternally-inherited germ plasm is specified and how it is transferred to primordial germ cells. Previous studies have shown that germ cells are first segregated at the embryonic posterior after formation of the blastoderm. We used two cross-reacting antibodies against the conserved germline markers Vasa and Nanos, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 38 publications
2
73
1
Order By: Relevance
“…In parthenogenetic aphids ( Acyrthosiphon pisum ; Hemiptera), which have a germ plasm, Nanos protein is more strongly expressed posteriorly in the oocyte, and this asymmetric expression is maintained through germ cell formation (Chang et al 2006 ). Posterior localization of Vasa also occurs shortly after fertilization (Lin et al 2014a ), whereas vasa and nanos mRNA are ubiquitously distributed in mature oocytes and only become localized posteriorly when germ cells form at the blastoderm stage (Chang et al 2007(Chang et al , 2009.…”
Section: Primordial Germ Cellsmentioning
confidence: 99%
“…In parthenogenetic aphids ( Acyrthosiphon pisum ; Hemiptera), which have a germ plasm, Nanos protein is more strongly expressed posteriorly in the oocyte, and this asymmetric expression is maintained through germ cell formation (Chang et al 2006 ). Posterior localization of Vasa also occurs shortly after fertilization (Lin et al 2014a ), whereas vasa and nanos mRNA are ubiquitously distributed in mature oocytes and only become localized posteriorly when germ cells form at the blastoderm stage (Chang et al 2007(Chang et al , 2009.…”
Section: Primordial Germ Cellsmentioning
confidence: 99%
“…Within the insects, some degree of maternal localization of nos has been observed in all species so far examined (Curtis et al, 1995;Lall et al, 2003;Goltsev et al, 2004;Chang et al, 2006;Dearden, 2006), indicating that the posterior patterning function of nos may be conserved.…”
Section: Introductionmentioning
confidence: 98%
“…As a consequence, oogenesis and embryogenesis occur within the ovariole. This morphological characteristic allows us to continuously observe how germ plasm is assembled during oogenesis, how it is incorporated into primordial germ cells, and how those cells migrate toward the somatic gonads (Brisson and Stern 2006;Chang et al 2006). Previous studies with cross-reacting antibodies have shown that the Nanos and Vasa proteins occur in the germarium, which lies at the anteriormost part of the telotrophic ovariole, and that they are localized to the posterior region of the egg chamber undergoing nuclear division.…”
Section: Introductionmentioning
confidence: 99%